INFLUENCE OF HEALTH EDUCATION THROUGH BOOKLET MEDIA ON PUBTER WOMAN KNOWLEDGE ABOUT EXCLUSIVE BREASTFEEDING AT PMB MURNIYATI - Azhari, Irma; Widyastutik, Desy; Putriningrum, Rahajeng (Universitas Kusuma Husada Surakarta, 2024)
As reported by the World Health Organization (WHO), less than half of infants under the age of six months worldwide are exclusively breastfed. In Indonesia, the proportion of infants who are exclusively breastfed has remained unchanged over the past two years. The Indonesian Nutrition Status Survey (SSGI) indicates that the prevalence of early breastfeeding initiation was 47.4 percent in 2021 and 58.1 percent in 2022. Additionally, the data for exclusive breastfeeding among infants aged 0-5 months was 52.1 percent in 2021 and 52.2 percent in 2022 (Saragih and Istianah, 2022). The objective of this study is to ascertain the impact of health education on postpartum mothers' knowledge regarding exclusive breastfeeding at PMB Murniyati. This study utilizes a quantitative research design with a quasi-experimental approach and a one-group pretest-posttest model. The sampling technique employed was total sampling, with a sample size of 30 individuals. The instrument utilized was a questionnaire designed to assess knowledge about exclusive breastfeeding. The data were analyzed using the Wilcoxon signed-rank test. The results of the study demonstrated that health education had a significant impact on postpartum mothers' knowledge and skills regarding the correct breastfeeding technique at PMB Murniyati. This was evidenced by a statistically significant difference in the pretest and posttest p-value (p < 0.05). The findings of this study indicate that health education has a significant impact on postpartum mothers' knowledge about exclusive breastfeeding at PMB Murniyati.